2017
DOI: 10.1016/j.ijdevneu.2017.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive deficits associated with a high‐fat diet and insulin resistance are potentiated by overexpression of ecto‐nucleotide pyrophosphatase phosphodiesterase‐1

Abstract: There is growing evidence that over consumption of high-fat foods and insulin resistance may alter hippocampal-dependent cognitive function. To study the individual contributions of diet and peripheral insulin resistance to learning and memory, we used a transgenic mouse line that overexpresses ecto-nucleotide pyrophosphatase phosphodiesterase-1 in adipocytes, which inhibits the insulin receptor. Here, we demonstrate that a model of peripheral insulin resistance exacerbates high-fat diet induced deficits in pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 65 publications
2
8
0
Order By: Relevance
“…Water Maze, AtENPP1Tg mice on HFD showed impaired performance as a behavioral correlate for reduced synaptic transmission (Kasper et al, 2018). Building on these results, in the current study, we identified synaptic plasticity deficits in the CA1 area could contribute to the cognitive decrements.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Water Maze, AtENPP1Tg mice on HFD showed impaired performance as a behavioral correlate for reduced synaptic transmission (Kasper et al, 2018). Building on these results, in the current study, we identified synaptic plasticity deficits in the CA1 area could contribute to the cognitive decrements.…”
Section: Discussionsupporting
confidence: 52%
“…We tested this hypothesis and observed that adipose tissue dysfunction during HFD intake has detrimental consequences in the cellular learning associated with the hippocampal circuitry required for learning, memory and cognitive function. In a previous study, we observed that in Morris Water Maze, At ENPP1 Tg mice on HFD showed impaired performance as a behavioral correlate for reduced synaptic transmission (Kasper et al, ). Building on these results, in the current study, we identified synaptic plasticity deficits in the CA1 area could contribute to the cognitive decrements.…”
Section: Discussionmentioning
confidence: 88%
“…Adiponectin, an anti-inflammatory cytokine, interacts with the brain by modulating inflammatory responses (Arnoldussen et al, 2014). Decreases in adiponectin may increase pro-inflammatory cytokine concentrations, which could lead to neuroinflammation and subsequent cognitive impairments (Kasper et al, 2017). In rodents, adiponectin is shown to have neuroprotective effects (Nishimura et al, 2008; Jeon et al, 2009; Ng and Chan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Insulin signaling has been reported to play an important role in cognitive function [ 39 , 40 ]. To further investigate the changes in insulin signaling after Hup A treatment, we tested the phosphorylation level of Akt at serine 473 (p-Akt), which is a necessary residue for Akt activity [ 41 ].…”
Section: Resultsmentioning
confidence: 99%